Influence of patient-related factors and surgeon experience on functional outcomes in conservatively treated proximal humerus fractures: a retrospective cohort study - Andrea Pautasso; Chiara Bernardi; Marco Assom; Davide Blonna; Federica Romano; Raffaele Garofalo; Alessandro Marinelli; Paolo Paladini; Filippo Castoldi; Enrico Bellato (European Journal of Orthopaedic Surgery & Traumatology, 2026)
Abstract Purpose Proximal humerus fractures (PHFs) are common in the elderly population, but the optimal treatment strategy remains controversial. This study evaluated the long-term functional outcomes of non-surgically treated PHFs and assessed whether retrospective treatment recommendations made by experienced shoulder surgeons were associated with differences in clinical outcomes. Materials and methods This retrospective cohort study included 150 PHFs in 149 patients treated nonoperatively between 2020 and 2021. Two-, three-, and four-part fractures with a minimum 12-month follow-up were analyzed. Outcome measures included QuickDASH, Oxford Shoulder Score (OSS), Subjective Shoulder Value (SSV), and SF-12. Demographic characteristics and radiographic fracture features were analyzed. In a second phase, five shoulder surgeons independently reviewed anonymized cases and retrospectively recommended surgical or conservative treatment while blinded to patient outcomes. Results At a mean follow-up of 32.1 months, younger age, absence of comorbidities, better pre-injury physical status, and dominant limb involvement were independently associated with superior outcomes, whereas the number of fracture fragments did not. Displaced fractures showed worse outcomes than non-displaced fractures. However, among displaced fractures, no significant differences in SSV, OSS, QuickDASH, or SF-12 scores were found between fractures retrospectively considered surgical candidates and those deemed suitable for conservative management. Conclusions Functional recovery following conservative treatment of PHFs appears to be influenced more by patient-related factors than by fracture morphology or surgeon experience. These findings suggest that carefully selected patients with displaced PHFs can achieve satisfactory outcomes with nonoperative treatment. Levels of evidence IV.